PENGARUH CAMPURAN SERAT ECENG GONDOK PADA LASTON TIPE II SPESIFIKSASI SNI 03-1737-1989 TERHADAP NILAI-NILAI MARSHALL - Triyoso Widianto; Dwi Kartikasari (Litbang Pemas - Universitas Islam Lamongan, 2019)
Laston is a mixture of long graded asphalt heat which consists of coarse, medium and fine aggregates. This mixture is called hot mix asphalt (hot mix asphalt) made or mixed in heat. In this mixture uses cellulose fibers derived from water hyacinth to find out whether water hyacinth fiber can be used as a mixture of hot asphalt and as a substitute for cellulose fibers in the market.In this study, the laboratory experimental research method is used to conduct experimental activities to produce a result of water hyacinth fiber mixing with Marshall Properties. The purpose of this study is to compare the results obtained at the optimum levels in the specifications of SNI 03-1737-1989 laston type II, with the addition of water hyacinth fiber variations of 0.3%, 0.5%, 0.7% taken from asphalt content .The final result of this research was Marshall evaluation which was obtained for the stability of 837 kg on 0.5% water hyacinth fiber content, 3.63 mm flow on 0.3% water hyacinth fiber content, Marshall Quotient 236.93 kg / mm in fiber content water hyacinth 0.7%, VIM 4.16% on water hyacinth fiber content 0.7%, VMA 16.68% on the water hyacinth fiber content of 07%, VFWA 75.70% on the level of water hyacinth 0.3% still meet the specifications limit. These results indicate that water hyacinth fiber can be used in a mixture of type II asphalt concrete (Laston) layers.